2018
DOI: 10.1167/iovs.18-24539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on Sirtuins, OPA1, and Fis1 Expression in Adult Zebrafish Retina

Abstract: To our knowledge, our study is the first composite analysis of sirtuins in adult zebrafish retina and provides sufficient evidence that resveratrol, as an activator of SIRT1, protects NMDA-induced zebrafish retinal damage by potentially mediating mitochondrial sirtuins and OPA1 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…We observed that the mtDNA integrity of young zebrafish retinas was increased after 1- or 10-days treatment with resveratrol, whereas the mitCN had a slight decrease after 10 days treatment but was not altered after only 1 day of treatment. One previous study found that resveratrol for one day can increase mtDNA integrity (the ratio of mit-L to mit-S) in adult zebrafish retinas but did not change the mitCN [30]. Another report indicated that resveratrol can decrease mitCN in mouse oocytes [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that the mtDNA integrity of young zebrafish retinas was increased after 1- or 10-days treatment with resveratrol, whereas the mitCN had a slight decrease after 10 days treatment but was not altered after only 1 day of treatment. One previous study found that resveratrol for one day can increase mtDNA integrity (the ratio of mit-L to mit-S) in adult zebrafish retinas but did not change the mitCN [30]. Another report indicated that resveratrol can decrease mitCN in mouse oocytes [52].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that the anti-aging effects of resveratrol are related to its ability to modulate mitochondria [28,29]. Resveratrol has been found to increase mitochondrial fusion/fission as well as promote Pink1 expression and autophagic activity [3033]. Additionally, some reports indicate these effects of resveratrol are due to its ability to decrease mammalian target of rapamycin (mTOR) levels and promote Ampk/Sirt1 activities [9,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular levels, mitochondrial fusion is primarily regulated by optic atrophy 1 (OPA1), which is predominately embedded in the mitochondrial membranes. Although the molecular mechanisms of mitochondrial fusion and mitophagy through OPA1 remain a matter of intense debate, increased OPA1 has been reported to be associated with active mitochondrial fusion and mitophagy by promoting the fusion of the inner mitochondrial membrane . In the atrial tissues of patients undergoing coronary artery bypass graft surgery, OPA1 is downregulated, and this process is connected with mitophagy delay .…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular mechanisms of mitochondrial fusion and mitophagy through OPA1 remain a matter of intense debate, 27 increased OPA1 has been reported to be associated with active mitochondrial fusion and mitophagy by promoting the fusion of the inner mitochondrial membrane. 28,29 In the atrial tissues of patients undergoing coronary artery bypass graft surgery, OPA1 is downregulated, and this process is connected with mitophagy delay. 30 Furthermore, decreased OPA1 is associated with the progression of autoimmune myocarditis via the repression of mitochondrial fusion.…”
Section: Introductionmentioning
confidence: 99%